Synthesis, Antibacterial and Antifungal Evaluation of Novel 3-(5-Phenyl[1,3,4]oxadiazol-2-yl]-3,4-dihydro-2H-benzo[e][1,3]oxazines - Vasu, N.; Bharath Kumar Goud, B.; Bharathi Kumari, Y.; Pulla Rao, B. (Asian Journal of Chemistry, 2014)
Various novel 3-(5-phenyl[1,3,4]oxadiazol-2-yl]-3,4-dihydro-2H-benzo[e][1,3]oxazines (5a-g) have been synthesized from 5-phenyl-[1,3,4]oxadiazol-2-ylamine (1) and different salicylaldehydes (2a-g) as starting materials and 2-[(5-phenyl[1,3,4]oxadiazol-2-ylimino)methyl]phenols (3a-g) and 2-[(5-phenyl[1,3,4]oxadiazol-2-ylamino)methyl]phenols (4a-g) as intermediates. The newly synthesized compounds after structural confirmation were used to screen their antibacterial, antifungal and nematicidal activities and some of these compounds have been found as potential antimicrobial agents.